Engineering materials and technology ICMSET 2016 - Jung, Jong Won (Key engineering materials,, 2017)
The readers will get acquainted with the newest research and solutions in the field of the applied materials engineering and technologies of materials processing and synthesis.We hope this volume will be of value for many researchers and engineers.